Estimation of Phenytoin Pharmacokinetic Parameters in Saudi Epileptic Patients - Alqahtani, Saeed; Alzaidi, Thuraya; Alotaibi, Mashal; Alsultan, Abdullah (Pharmacology, 2019)
This study aimed to assess the population pharmacokinetics of phenytoin in Saudi patients and identify factors affecting therapeutic parameters. A retrospective chart review was performed at King Saud University Medical City on patients treated with oral phenytoin. We used Monolix 4.4. for population pharmacokinetic modeling. A base model was developed to investigate several covariates, including age, gender, weight, total daily dose (TTD), and liver function test results. The analysis included a total of 81 phenytoin plasma concentrations from 43 patients (70% male). Patients' mean (± SD) age was 41 (±18.7) years and body weight was 65.4 (±17.7) kg. The patients received a phenytoin TDD of 330.5 (±104.5) mg/day, resulting in a trough concentration of 11.2 (±10.3) mg/L. The data were sufficiently described by the one-compartment open model with linear absorption and nonlinear elimination processes. Average parameter estimates for phenytoin volume of distribution (V), maximal elimination rate (Vmax), and Michaelis-Menten constant (Km) were 0.61 L/h/kg, 6.12 mg/kg/day, and 5.33 mg/L, respectively. The most significant covariates on phenytoin Vmax and Km were the age and body weight of the patients, along with valproic acid (VPA) cotherapy. The population pharmacokinetic model of phenytoin in Saudi patients found significant interindividual variability between subjects, which was affected by the patients' age, body weight, and VPA cotherapy as the most significant covariates on phenytoin Vmax and Km. To provide guidance in drug dosage decisions, further studies are required to evaluate all factors that may potentially influence the pharmacokinetics of phenytoin.